2017
DOI: 10.1113/ep086374
|View full text |Cite
|
Sign up to set email alerts
|

One minute static stretch of plantar flexors transiently increases H reflex excitability and exerts no effect on corticospinal pathways

Abstract: What is the central question of this study? What mediates neural responses following static stretching, and how long do these influences last? What is the main finding and its importance? This study shows that 1 min of static stretching inhibits the tendon tap reflex and facilitates the H reflex without influencing motor-evoked potentials. The results indicate that at least two different mechanisms mediate neural responses after static stretching. The purpose of this study was to determine whether the neural r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 38 publications
1
44
2
Order By: Relevance
“…This is in agreement with other studies that have not detected changes in spinal excitability using this measure, even at rest, after a bout of static stretching [5,13,14]. In fact, according to a recent review [42], even when H-reflex depression has been observed as long as 2 s after the removal of a muscle stretch, it certainly appears to be recovered within 15 s. For example, Budini et al [16] observed an increase in H-reflex after one minute of static stretching, but it returned to baseline values by 40-50 s after stretching. This is consistent with the method adopted in the present study, in which H-reflex was recorded 40-50 s after the conclusion of stretching.…”
Section: Spinal Excitabilitysupporting
confidence: 91%
See 3 more Smart Citations
“…This is in agreement with other studies that have not detected changes in spinal excitability using this measure, even at rest, after a bout of static stretching [5,13,14]. In fact, according to a recent review [42], even when H-reflex depression has been observed as long as 2 s after the removal of a muscle stretch, it certainly appears to be recovered within 15 s. For example, Budini et al [16] observed an increase in H-reflex after one minute of static stretching, but it returned to baseline values by 40-50 s after stretching. This is consistent with the method adopted in the present study, in which H-reflex was recorded 40-50 s after the conclusion of stretching.…”
Section: Spinal Excitabilitysupporting
confidence: 91%
“…It could underpin facilitatory mechanisms located at cortical, spinal and motoneuronal levels [22], and would be primarily related to input from stretch-sensitive afferents [4,14,34] during static stretching and dynamic muscle activity. This ongoing increase is inconsistent with the current literature, which has reported a decrease in MEP amplitude during static stretching itself, which then returned to baseline values as soon as stretching was ended [14,16]. Moreover, a recent study revealed an increase in MEP amplitude up to 2 s following stretching, which then quickly recovered to initial values [17].…”
Section: Corticospinal Excitabilitycontrasting
confidence: 84%
See 2 more Smart Citations
“…Conditioning a muscle by means of stretching induces changes not only in muscle compliancy (Konrad et al, 2017 ), but also in discharge and sensitivity of muscle spindles (Gregory et al, 1987 ), excitability of spinal pathways (Budini et al, 2017 ), and cortical excitability (Stuart et al, 2002 ). However, from a neuromuscular point of view there seems to be a noticeable difference between conditioning the muscle through static stretching (passively holding a static position with the muscle lengthened) and through a passive eccentric movement (single non-active lengthening movement).…”
Section: Introductionmentioning
confidence: 99%